Особливості цвітіння та плодоношення Schisandra chinensis (Turcz.) Baill. за умов інтродукції в Правобережному Лісостепу України - Sliusar, G.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2018)
Objective – to investigate of peculiarities of biology of flow ering and fruiting of Schisandra chinensis (Turcz.) Baill. under conditions of introduction in the Right-Bank of Forest-Steppe of Ukraine. Material and methods. The study was carried out in 2016–2017 with using of standart methods. The subject of research were the plants of S. chinensis from the collection of the acclimatization department of fruit plants of M.M. Gryshko National Botanical Garden of NAS of Ukraine. Results. The biology of the development of S. chinensis is explored under conditions of the introduction in the Right-Bank of Forest-Steppe of Ukraine. The duration of the vegetative period from the beginning of the spring sap to the complete fall of the leaves on the base of longterm studies is an average 200 days. The beginning of the flowering phase of S. chinensis is marked in the third decade of April for the sum of effective temperatures 351.9–424.7 °C. Flowering lasts on the average 28 days regardless of weather conditions. The barking of the fruits depends on the average daily temperature of the air during the flowering period of the plants: cold rainy weather prevents the flying of insects and consequently the pollination of flowers, as a result of which there is a small number of fruit on the fennel (1–5). Under favorable conditions the index of fruit barking reaches an average of 88 %. The beginning of maturation of the fruit of the S. chinensis is noted at the end of August for the sum of effective temperatures 2673.9–2690.7 °C. Conclusions. In conditions of introduction in the Right-Bank of Forest-Steppe of Ukraine plants of S. chinensis pass full-cycle of their development and are promising for wide introduction in the gardening. Two-domed plants with samesex flowers were found in the S. chinensis introductive population, which should be taken into account when using seedling material of seed origin. High indicators of the fertility and viability of the S. chinensis pollen were revealed.